EQUILIBRIUM CONDITION AND LOCOMOTION PROBLEMS IN BROILERS - ALVES, M.C.F.; ALMEIDA PAZ, I.C.L.; CALDARA, F.R.; NÄÄS, I.A.; GARCIA, R.G.; SENO, L.O.; BALDO, G.A.A.; AMADORI, M.S. (Revista Brasileira de Engenharia de Biossistemas, 2013)
Poultry growth depends particularly of muscle development as well as their bone tissue. Nowadays in broilers, muscle growth is extremely raised while their skeletal support is still very immature, having as consequence the onset of locomotor disorders among others. With advances in poultry breeding, its found that gait and equilibrium condition were negatively impacted, causing mobility problems in these animals. The current review presents the main locomotor disorders that affect poultry and some of the factors that influence them, as well as the impact they cause in poultry production.